THE RETENTION DIAGRAM OF POLY(P-CHLOROSTYRENE) AND TERT-BUTYL ACETATE BY THE INVERSE GAS-CHROMATOGRAPHY METHOD - CANKURTARAN, O; YILMAZ, F (MARCEL DEKKER INC, 1993)
The retention diagram of poly(p-chlorostyrene) for tert-butyl acetate was obtained by the inverse gas chromatograhy method. This polymer-solvent pair exhibits a lower critical solution temperature, i.e., the solubility of the polymer in the solvent decreases with temperature. The obtained retention diagram of this polymer-solvent system contained an extra region with a negative slope at temperatures lower than 90-degrees-C. It appears that in this region, the favorable specific interactions between the polymer and the solvent can be observed. The weight fraction activity coefficient OMEGA1 infinity and the Flory-Huggins interaction parameter chi12infinity at infinite dilution and the effective exchange interation parameter chi12BAR of the system were calculated. These values confirm that the tert-butyl acetate is a poor solvent for this polymer, at 160-degrees-C.
Keywords: Polymer Science